Network Pharmacology and Transcriptomic Sequencing Analyses Reveal the Molecular Mechanism of Sanguisorba officinalis Against Colorectal Cancer - Zhang, Weijia; Sang, Shuyi; Peng, Chang; Li, George Q.; Ou, Ling; Feng, Zhong; Zou, Yuanjing; Yuan, Yuemei; Yao, Meicun (Frontiers in Oncology, 2022)
Background: Colorectal cancer (CRC) is the most common malignant cancer worldwide. Sanguisorba officinalis has been shown to have anti-inflammatory, anti-bacterial, antioxidant and anti-tumor effects, while its molecular mechanism against CRC remains unclear. The aim of this study was to explore the underlying mechanism of S. officinalis against CRC cell lines using network pharmacology and transcriptomic sequencing methods. Method: Firstly, active ingredients and potential targets of S. officinalis against CRC were screened from databases. Secondly, the ingredient-target, ingredient-target-CRC, were constructed with protein-protein interaction (PPI) networks, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses of network pharmacology and transcriptomic sequencing were performed. Finally, the effect of S. officinalis against CRC was verified by in vitro experiments. Results: 14 active ingredients and 273 potential targets against CRC were identified in S. officinalis by network pharmacology. PI3K-Akt, HIF-1 and MAPK signaling pathways related to cell proliferation were regulated by S. officinalis in enrichment analyses and transcriptomic sequencing. In vitro, S. officinalis inhibited proliferation and migration of CRC cells, and arrested cell cycle at G0-G1 phase. Western blot showed that S. officinalis down-regulated the expression of p-PI3K, p-Akt, HIF-1A, VEGFA, Cyclin D1, c-Myc, p-MAPK proteins in CRC cells. Conclusion: In conclusion, network pharmacology and transcriptomic sequencing analysis, in combination with in vitro studies, have been successfully applied to study the underlying mechanism of Sanguisorba officinalis against CRC cells. Our results demonstrate that S. officinalis suppresses the proliferation, survival, and migration of CRCcells through regulating PI3K-Akt, HIF-1 and MAPK signaling pathways.